RESPON PERTUMBUHAN TANAMAN CABAI RAWIT (Capsicum frutescens L.) TERHADAP KONSENTRASI DAN FREKUENSI EKOENZIM - Sulastri, Yustina Sri (LPPM Universitas Katolik Santo Thomas Medan, 2023)
Chili, which is one of the seven national strategic commodities, shows fluctuating export figures and import figures that tend to increase. It is necessary to implement a cultivationtechnology to increase the growth of chili plants. One technique for cultivating chilies usesecoenzymes. Research to see the effect of ecoenzymes on the growth of cayenne pepper plants hasbeen carried out. This research used a factorial Randomized Block Design (RBD), namelythe first factor was the ecoenzyme concentration consisting of 4 treatment levels, namely: K0 : 0ml/500 ml water, K1 : 15 ml/500 ml water, K2 : 30 ml/500 ml water, K3: 45 ml/500 ml water. The second factor is the frequency of ecoenzymes consisting of 3 treatment levels, namely: F1: 1time a week, F2: 2 times a week, F3: 3 times a week. Statistical testing was carried out by compiling a list from analysis of variance. For treatments that had a significant effect, a mean difference test was carried out with an honest significant difference test at the 5% level and continued with regression analysis. The parameters observed were plant height (cm), number of leaves (strands),stem diameter (cm). The results showed that both concentration and frequency factors did not have a significant influence on all parameters except the number of leaves parameter. The increasing ecoenzyme concentration to 45 ml/500 ml of water increased the number of leaves by 49.59 pieces.